Water quality parameters and nutrient status of selected reservoirs in Tamil Nadu, India - T. Deepak; P. Padmavathy; V. Rani; D. Manimekalai; Devasena, S. Subhashree (Indian Journal of Fisheries, 2022)
The present study was undertaken to assess the interrelation between water quality and nutrient status of three reservoirssituated in Tamil Nadu, India. These three reservoirs are managed by the Public Works Department (PWD) with the fisheriesaspects falling under the purview of Tamil Nadu State Fisheries Department. In each reservoir, inflow and outflow sectionswere identified as sampling sites. A total of six sampling sites were fixed and monthly sampling for water and fish wasconducted during the period from October 2019 to June 2020. The various physico-chemical parameters such as temperature,electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), total volatile solids (TVS), turbidity,DO, pH, alkalinity, hardness, chloride, sulphate, biological oxygen demand (BOD) and chemical oxygen demand (COD)were analysed. Biological parameters like chlorophyll-a and primary production as well as various nutrient parameterswere also analysed in the collected water samples. All the physical and chemical water quality variables showed significantvariation (p